Performance Estimation of Adaptive Fuzzy Logic Speed Controller for Reduced Switch BLDC Motor Drive. Issue 1 (June 2021) - Krishna Veni, K.S.; Senthil Kumar, N.; Gnanavadivel, J.
Abstract: This article deals with the implementation of an adaptive fuzzy logic based reduced switch brushless DC motor drive. In topological view, the cost of the system chiefly depends upon the power semiconductor switches. Hence switch reduction concept is adapted in this paper. The operating principle, switching sequence formulation of reduced switch topology is presented. An intelligent system for reduced switch BLDC drive is designed and tested for different load conditions. Simulation results as well as comparative performance with conventional controllers are presented and discussed. The parameters such as rise time and steady state error are observed. The effectiveness and robustness of the reduced switch BLDC drive for variable speed applications is demonstrated. The rise time and steady state error of the proposed system is improved about an average of nearly 60% and 30% respectively compared to other controllers.